2021
DOI: 10.21037/gs-20-740
|View full text |Cite
|
Sign up to set email alerts
|

Intracorporeal versus extracorporeal urinary diversion after robot‐assisted radical cystectomy: a pooled analysis

Abstract: Background: To compare intracorporeal urinary diversion (ICUD) with extracorporeal urinary diversion (ECUD) after robot-assisted radical cystectomy (RARC) for surgery safety, postoperative recovery, complication, and prognosis. Methods:We performed a literature search on PubMed, Embase, Medline and the Cochrane Library based on all randomized controlled trials (RCTs) and observational comparative studies related to study topics published before July 14th, 2020. Then systematic review and meta-analysis was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
(25 reference statements)
2
4
0
Order By: Relevance
“…Regarding postoperative complications within 90 days, grade ≥ 3 complications such as surgical site infection, pelvic abscess, and anastomotic urine leak were more common in the ECUD group than in the ICUD and HUD groups. Hussein et al reported a signi cantly higher incidence of infection in the ICUD group [14], but no other studies have reported higher incidences of surgical site infection and pelvic abscess in the ECUD group [12,13,[15][16][17][18][19]. Our study also showed that ICUD did not increase wound infections or pelvic abscesses caused by the spread of intestinal bacteria into the abdominal cavity.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Regarding postoperative complications within 90 days, grade ≥ 3 complications such as surgical site infection, pelvic abscess, and anastomotic urine leak were more common in the ECUD group than in the ICUD and HUD groups. Hussein et al reported a signi cantly higher incidence of infection in the ICUD group [14], but no other studies have reported higher incidences of surgical site infection and pelvic abscess in the ECUD group [12,13,[15][16][17][18][19]. Our study also showed that ICUD did not increase wound infections or pelvic abscesses caused by the spread of intestinal bacteria into the abdominal cavity.…”
Section: Discussionsupporting
confidence: 48%
“…In RC, the bladder should not be removed, but UD should be performed subsequently. ECUD or ICUD as the more ideal UD technique with fewer complications remains debatable [12][13][14][15][16][17][18][19]. Additionally, comparison of HUD with ECUD and ICUD has not yet been reported; thus, this study is the rst to report it.…”
Section: Discussionmentioning
confidence: 99%
“…Several meta-analyses have been published in the last two years that aggregate large amounts of data to compare iRARC, eRARC, and ORC [35–46]; they report similar findings as above. Generally, when comparing RARC (inclusive of both intracorporeal and extracorporeal technique) and ORC they report equivalent oncological outcomes and an advantage in lower EBL, lower transfusion rates, shorter length of stay, and quicker return to regular diet.…”
Section: Intracorporeal Urinary Diversionsupporting
confidence: 57%
“…All the urinary diversions in the RAZOR trial were performed extracorporeally, which can influence complication results [6] . However, performing the urinary diversion in an extracorporeal or intracorporeal way also carries similar complication rates, with a trend towards less gastrointestinal complications in the intracorporeal urinary diversion [7,8] . Early complications are less related to the type of urinary diversion than late complications [3] .…”
Section: Early Post-operative Complications (90 Days)mentioning
confidence: 99%
“…Each diversion type has its own specific complication, related not only to the construction of the diversion but also to the chosen intestinal segment. The surgical approach (open vs. robot-assisted and extracorporeal vs. intracorporeal) is not related to specific complications [6,7] .…”
Section: Diversion Specific Complicationsmentioning
confidence: 99%